Safety and Efficacy of Hypofractionated Stereotactic Radiosurgery in Facial Nerve Schwannoma. Issue 8 (28th September 2022) - Fatima, Nida; La Dine, Anna K.; Barnard, Zachary R.; Ko, Katherine; Peng, Kevin; Slattery, William H.; Lekovic, Gregory P.
Abstract : Objective: In the current era of modern neurosurgery, the treatment strategies have been shifted to "nerve-preservation approaches" for achieving a higher facial and hearing function preservation rate following facial nerve tumors. We have conducted this novel report on determining the outcome of patients with facial nerve schwannomas (FNS) treated with hypofractionated stereotactic radiosurgery (hfSRS). Patients: Retrospective chart review of a prospectively maintained database search was conducted. Intervention: Patients who underwent hfSRS CyberKnife (Accuray Inc, Sunnyvale, CA, U.S.A.) for FNS were included. Main Outcome Measures: Outcomes consisted of tumor control, facial and hearing nerve function as graded by House-Brackmann and American Academy of Otolaryngology-Head and Neck Surgery recommendations, and adverse radiation effects. Results: With an institutional board review approval, we retrospectively identified five patients with FNS (four intracranial [80%] and one extracranial [20%]) treated with hfSRS (2011–2019). Patients received definitive SRS in three patients (60.0%), whereas adjuvant to surgical resection in two patients (40.0%). A median tumor volume of 7.5 cm 3 (range, 1.5–19.6 cm 3 ) received a median prescription dose of 23.2 Gy (range, 21–25 Gy) administered in median of three fractions (range, three to five sessions). With a median radiographic follow-up of 31.4 months (range, 13.0–71.0 mo) and clinical follow-up of 32.6 months (range, 15.1–72.0 mo), the local tumor control was 100.0%. At the last clinical follow-up, the facial nerve function improved or remained unchanged House-Brackmann I–II in 80.0% of the patients, whereas the hearing nerve function improved or remained stable in 100.0% of the patients. Temporary clinical toxicity was observed in three patients (60.0%), which resolved. None of the patients developed adverse radiation effect. Conclusion: From our case series, hfSRS in FNS seems to be safe and efficacious in terms of local tumor control, and improved facial and hearing nerve function.